تقييم ثلاثة أصناف من الطماطةLycopersicon esculentmتحت ظروف منطة دهوك - سرحان, طه زبير; سعي, مصلح محمد; درويش, عبدالله جوقي (Sulaimani Journal for Pure and Applied Sciences, 2002)
In a field experiment during two successive seasons, the response of two imported tomato cultivars were studied and compared with that of local cultivar. results indicated that the average fruit weight , early yield , medium, yield and total yield were found to be higher for both Humanitas and super Beta cultivars as compared with that of local cultivar. while the local cultivar succeeded on the other two cultivars in the character of average plant height, branch numbers and subsequently average inflorescence and total flowers number per plant.
Keywords: super BetaSB; Humanitas H; Local variety L